Genome assembly of Luehdorfia taibai, an endangered butterfly endemic to Qinling Moutains in China with extremely small populations - Guan, De-Long; Zhao, Lu; Li, Yufei; Xing, Lian-Xi; Huang, Huateng; Xu, Sheng-Quan (Frontiers in Ecology and Evolution, 2022)
Conservation genomic resources over the past decade has drastically improved, since genomes can be used to predict diverse parameters vital to conservation management. Luehdorfia taibai is an endemic butterfly only found in restricted aeras in middle-west China and is critically endangered. It was classfied as a vunerlable (VN) species in the “China species red list”. Here we generated 34.38 Gb of raw DNA sequencing reads and obtained a high-qualified draft genome assembly of L. taibai. The final genome is ~ 683.3 Mb, with contig N50 size of 10.19 Mb. Further, 98.6% of single-copy orthologous genes have been recovered by BUSCO. An estimated 42.34% of the genome of L. taibai consists of repetitive elements. Combined with gene prediction and transcriptome sequencing, genome annotation produced 15,968 protein-coding genes. Additionally, a nearly 1：1 orthology ratio of syntenic blocks between L. taibai and its closest genome Luehdorfia chinensis suggested that the genome structures have not changed much after speciation. The genome of L. taibai have not undergone a whole genome duplication event. Population dynamics analyses indicates that L. taibai has an extremely low heterozygosity of 0.057%, and its population size has declined dramatically over the past 10 thousand years. Our study describes a draft genome assembly of the L. taibai, the first implication of this species. We consider the globally overexploited of the host plants is not the main reason to threaten L. taibai. The genome will provide advice for the conservation to the economically important Luehdorfia lineage and this specific species.